Hyperparasitism by Viscum monoicum Roxb. ex DC. on Dendrophthoe falcata (L.F.) Ettingsh: A Novel Case Reported from Nepal - Devkota, Mohan Prasad (Journal of Institute of Science and Technology, 2024)
A rare occurrence of Viscum monoicum Roxb. ex DC. (Viscaceae) on Dendrophthoe falcata (L.F.) Ettingsh. (Loranthaceae) has been reported as a novel case of incidental hyperparasitism for the first time from the tropical forests of Nepal.